Azolla Anabaena como suplemento alternativo para alimentar tilapias (oreochromis niloticus) y abaratar costos de producción - Reyes Palma, Heidy Nicolasa (2021)
A bibliography research was carried out with the objective of knowing new food alternatives for the production of tilapia. Given that in aquaculture the increase in food prices, alteration in the supply and scarcity of the same, constitute new risks that can endanger the functioning of this sector, it seemed very appropriate to carry out an investigation to find new alternatives feeding for tilapias as long as they contain benefits and nutrients. Greatly, there are local products recognized as unconventional foods, such is the case of aquatic plants (Azolla Anabaena), which are not regularly used in animal nutrition, but well used can become a significant element in sustainable production systems. Especially because it has a low economic cost, likewise we cannot that some of them accumulate in settled places; they can become polluting elements of the environment.